2007
DOI: 10.1074/jbc.m611612200
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Sarafotoxins as Tissue Inhibitor of Metalloproteinases-like Matrix Metalloproteinase Inhibitors

Abstract: The sarafotoxins and endothelins are ϳ25-residue peptides that spontaneously fold into a defined tertiary structure with specific pairing of four cysteines into two disulfide bonds. Their structures show an interesting topological similarity to the core of the metalloproteinase interaction sites of the tissue inhibitors of metalloproteinases. Previous work indicates that sarafotoxins and endothelins can be engineered to eliminate or greatly reduce their vasopressive action and that their structural framework c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Modification of TIMPs can improve their selectivity within the MMP family [9698]. Mini-TIMPs have been constructed using the sarafotoxin 6b fold [46], with the sarafotoxin 6b C -terminal residues VIW deleted to remove vasopressive activity. Substitutions were incorporated to make the sarafotoxin 6b sequence more “TIMP-like.” The best inhibitor was STX-S4-CT (CSCSDMTDKECLYFCMSEMS), which inhibited MMP-1 and MMP-9 with K i = 4.5 and 1.0 µM, respectively.…”
Section: Inhibitors Of Matrix Metalloproteinasementioning
confidence: 99%
“…Modification of TIMPs can improve their selectivity within the MMP family [9698]. Mini-TIMPs have been constructed using the sarafotoxin 6b fold [46], with the sarafotoxin 6b C -terminal residues VIW deleted to remove vasopressive activity. Substitutions were incorporated to make the sarafotoxin 6b sequence more “TIMP-like.” The best inhibitor was STX-S4-CT (CSCSDMTDKECLYFCMSEMS), which inhibited MMP-1 and MMP-9 with K i = 4.5 and 1.0 µM, respectively.…”
Section: Inhibitors Of Matrix Metalloproteinasementioning
confidence: 99%
“…[24][25][26] Collagenolytic activities and MMP inhibition have been largely studied on triple-helical synthetic substrates. 27,28 Also, the role of the CBD exosite in modulating type I collagen degradation has been extensively documented. [29][30][31][32][33][34] Nevertheless, despite the importance of type IV collagen degradation, it has been little studied.…”
Section: Introductionmentioning
confidence: 99%
“…This protein naturally contains the CSCS N‐terminal motif. A previous study showed that a truncated analogue of the related miniprotein sarafotoxin 6b possessing a similar fold to that of endothelin‐1 and a CSCS N‐terminal motif was capable of inhibiting MMP‐1, MMP‐2 and MMP‐9 with affinities between 1 and 20 μ m . In this work, the authors identified sarafotoxin 6b as a suitable scaffold based on its N‐terminal 1D sequence homology with TIMPs.…”
Section: Discussionmentioning
confidence: 93%